(untitled) (Scientia Agropecuaria, 2020)
The present study aimed to determine the concentrations of As, Cd, Pb and Hg in soil and crops (banana and cassava) in areas abandoned by gold mining, southeast of the Peruvian Amazon. The concentration and bioaccumulation of heavy metals was analyzed, according to the plant organ (root, stem, leaf and fruit). Soil Hg concentrations (< 0.01 mg/kg) were found to be similar in contaminated and uncontaminated plantations; while the concentrations of As, Cd and Pb were higher in the contaminated ones. The concentrations of As, Pb and Cd in cassava and banana were higher in the contaminated plantations. In cassava, a high accumulation of Pb and As was found in the roots and stems (> 2.9 mg/kg). In banana fruits, the lowest concentrations of all the metals analyzed were found (< 0.01 mg/kg). The degree of bioaccumulation of As and Pb was intense for cassava in contaminated areas. The concentrations of As and Pb in cassava roots exceed the levels recommended by the FAO/ WHO. For these reasons, evaluation, monitoring and greater control in the commercialization of agricultural products cultivated in areas abandoned by gold mining are essential to avoid toxicity in humans.